Ta’zir Punishment in the Mazhab Syafi’i and Its Application in Syariah Court of Brunei Darussalam - Nurul Aqilah binti Othman; Cecep Soleh Kurniawan; Norasiah binti Haji Amai; Muhammad Zakir bin Husain; Muallimin Mochammad Sahid (Al-Mazaahib: Jurnal Perbandingan Hukum, 2026)
Ta’zir refers to discretionary punishments imposed for offences not covered by Hudud or Qisas. In Brunei Darussalam, ta’zir is codified under the Syariah Penal Code Order 2013 (SPCO 2013). This study examines the application of ta’zir punishments in Brunei Darussalam, focusing on the extent to which contemporary Syariah criminal practice reflects the principles of the Mazhab Syafi’i as the country’s official Mazhab. The main question addressed in this article concerns how classical Syafi’i Fiqh on ta’zir is translated into a modern, codified legal system and what tensions arise in this process. This research adopts a normative legal method, relying on doctrinal analysis of classical Syafi’i fiqh sources alongside Brunei’s Syariah criminal legislation and related legal documents. A comparative approach is employed to identify points of convergence and divergence between classical jurisprudence and contemporary judicial practice. The findings indicate that the implementation of ta’zir in Brunei is predominantly grounded in Syafi’i principles, particularly regarding judicial discretion, deterrence and the protection of public welfare. The originality of this study lies in its identification of Brunei’s ta’zir framework as a hybrid model that selectively adapts classical Syafi’i doctrine to contemporary governance requirements, contributing to broader discussions on the harmonization of Islamic Jurisprudence and modern criminal law.